Effects of coronal leakage on concentration of hydrogen ions and calcium hydroxide release of several calcium hydroxide pastes over different periods of time - Crespo, Mariana Pires; Kuga, Milton Carlos [UNESP]; Só, Marcus Vinicius Reis; Keine, Katia Cristina [UNESP]; Shinohara, André Luis (My University, 2013)
Purpose: To evaluate the effects of coronal leakage on concentration of hydrogen ions (pH) and calcium release of several calcium hydroxide pastes, over different periods of time. Material and Methods: Fifty extracted human mandibular central incisors (n=10) were instrumented up to the F2 instrument and assigned to the following intracanal dressing: G1- Calen, G2- Calen with 0.4% chlorhexidine (CHX), G3- Calcium hydroxide with camphorated paramonochlorophenol (CPMC) and glycerin, G4- Calen, but temporary filling material maintained during all test (positive control) and G5- Root canal without intracanal dressing (negative control). All groups were immersed in distilled water for 7 days. In sequence, the temporary filling materials were removed, except in controls groups. All specimens were individually mounted on a specific device and only its root again immersed in distilled water. Concentration of hydrogen ions and calcium release by calcium hydroxide pastes in distilled water were evaluated in 24h, 7, 14 and 28 days. The results were submitted to ANOVA test (p = 0.05). After 28 days, root canals from experimental groups were examined in SEM. Results: G1, G2, G3 and G4 presented similar pH values and calcium release and did not differ from each other (p>0.05), up to 7 days. After this time G1, G2 and G3 presented values lower values than G4 (p<0.05). In SEM analysis, calcium hydroxide residues were observed in all experimental groups. Conclusions: After 7 days, coronal leakage decreased the concentration of hydrogen ions and calcium ion release provided by all calcium hydroxide pastes.
Keywords: Calcium; Camphorated parachlorophenol; Chlorhexidine; Hydrogen; Scanning electron microscopy